miR372 Promotes Progression of Liver Cancer Cells by Upregulating erbB-2 through Enhancement of YB-1 - Zhuojia Lin; Yanan Lu; Qiuyu Meng; Chen Wang; Xiaonan Li; Yuxin Yang; Xiaoru Xin; Qidi Zheng; Jie Xu; Xin Gui; Tianming Li; Hu Pu; et al. (Elsevier, 2018)
MicroRNAs are known to be involved in carcinogenesis. Recently, microRNA-372 (miR372) has been proven to play a substantial role in several human cancers, but its functions in liver cancer remain unclear. Herein, our results demonstrate that miR372 accelerates growth of liver cancer cells in vitro and in vivo. Mechanistically, miR372 enhances expression of Y-box-binding protein 1 (YB-1) by targeting for phosphatase and tensin homolog (PTEN) directly and consequently promotes phosphorylation of YB-1 via HULC looping dependent on ERK1/2 and PTEN. In particular, HULC knockdown or PTEN overexpression abrogated this miR372 action. Moreover, miR372 inhibits the degradation of β-catenin dependent on phosphorylation of YB-1 and then enhances the expression and activity of pyruvate kinase M2 isoform (PKM2) by β-catenin-LEF/TCF4 pathway. Furthermore, the loading of LEF/TCF4 on PKM2 promoter region was significantly increased in miR372 overexpressing Hep3B, and thus, glycolytic proton efflux rate (glycoPER) was significantly increased in rLV-miR372 group compared to the rLV group. Moreover, β-catenin knockdown abrogates this function of miR372. Ultimately, miR372 promotes the expression of erbB-2 through PKM2-pH3T11-acetylation on histone H3 lysine 9 (H3K9Ac) pathway. Of significance, both YB-1 knockdown and erbB-2 knockdown abrogate oncogenic action of miR372. Our observations suggest that miR372 promotes liver cancer cell cycle progress by activating cyclin-dependent kinase 2 (CDK2)-cyclin E-P21/Cip1 complex through miR372-YB-1-β-catenin-LEF/TCF4-PKM2-erbB-2 axis. This study elucidates a novel mechanism for miR372 in liver cancer cells and suggests that miR372 can be used as a novel therapeutic target of liver cancer.